2003
DOI: 10.1596/1813-9450-3159
|View full text |Cite
|
Sign up to set email alerts
|

Does Judicial Efficiency Lower the Cost of Credit?

Abstract: We investigate the effect of judicial efficiency on banks' lending spreads for a large cross section of countries. We measure bank interest rate spreads for 106 countries at an aggregate level and for 32 countries at the level of individual banks. We find that, after controlling for a number of other country characteristics, judicial efficiency, in addition to inflation, is the main driver of interest rate spreads across countries. This suggests that in addition to improving the overall macroeconomic climate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 16 publications
7
81
1
2
Order By: Relevance
“…While in Albania there are four loans per 1,000 people, there are almost 800 loans per 1,000 people in Poland (Beck, Demirguc-Kunt and Martinez Peria, 2005). While interest rate spreads -the difference between lending and deposit rates -vary typically between two and four percent in developed financial systems, they are over 30% in Brazil (Laeven and Majnoni, 2005).…”
Section: Mozambiquementioning
confidence: 99%
See 1 more Smart Citation
“…While in Albania there are four loans per 1,000 people, there are almost 800 loans per 1,000 people in Poland (Beck, Demirguc-Kunt and Martinez Peria, 2005). While interest rate spreads -the difference between lending and deposit rates -vary typically between two and four percent in developed financial systems, they are over 30% in Brazil (Laeven and Majnoni, 2005).…”
Section: Mozambiquementioning
confidence: 99%
“…More effective legal systems provide for more flexible, adaptable and rapid conflict resolution rather than rigid, lengthy statutorily based processes with positive repercussions for firms' access to finance (Djankov et al, 2003;Beck, Demirguc-Kunt and Levine, 2005). Cross-country comparisons have shown that financial systems that can rely on more effective legal systems, have lower interest rate spreads and are more efficient (DemirgucKunt, Laeven and Majnoni, 2005). …”
Section: Contractual Frameworkmentioning
confidence: 99%
“…The effect that better judicial efficiency and judicial enforcement (as measured by the degree of property rights protection and the rule of law) lower the interest rate spreads of banks is confirmed by Laeven and Majnoni (2005) for a large crosssection of countries. Jappelli et al (2005) study the effect of the quality of legal enforcement (as measured by the length of trials and the stock of pending trials) on the interest rate.…”
Section: Empirical Implicationsmentioning
confidence: 83%
“…Their second finding of a negative relationship between creditor rights and interest rates is confirmed by Aggarwal and Kyaw (2004), who also investigate the effects of the host country environment on the capital structure of MNC affiliates. Similarly, Laeven and Majnoni (2005) find that judicial efficiency is negatively correlated with interest rate spreads across countries.…”
mentioning
confidence: 85%